Increasing resistant starch of processed Thai rice using citric acid, extra virgin coconut oil and herbs - Poomsa-ad, Nattapol; Suwannarong, Sarinthorn; Pakdeenarong, Noppakun; Wiset, Lamul (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2024)
This study aimed to increase resistant starch (RS) content in cooked KDML 105 rice. Various factors were investigated, such as rice type, cultivation area, oil type, rice cooker, and Thai herbs. This study found that the choice of oil and the incorporation of specific Thai herbs had a significant impact on the RS content of cooked KDML 105 rice. Using extra virgin coconut oil increased RS content, while certain Thai herbs, particularly Pandan leaves juice and butterfly pea flower, contributed to both increased RS content. Sao Hai rice had the highest RS content (4.31 ± 0.30 %). Saline soil areas did not significantly affect RS content in KDML 105 rice. Using extra virgin coconut oil and pressure rice cookers increased RS content significantly (1.40 ± 0.23 %). Incorporating four Thai herbs improved RS content. Notably, soaking rice in 2 % citric acid, mixing with extra virgin coconut oil, Thai herb and pressure cooking significantly increased RS content.